Urban drainage control applying rational method and geographic information technologies - Aldalur, Nélida Beatriz (2013)
The objective of this study is to develop a method of controlling urban drainages in the town of Ingeniero White motivated by the problems arising as a result of floods, water logging and the combination of southeasterly and high tides. A Rational Method was applied to control urban watersheds and used tools of Geographic Information Technology (GIT). A Geographic Information System was developed on the basis of 28 panchromatic aerial photographs of 2005. They were georeferenced with control points measured with Global Positioning Systems (basin: 6 km2). Flow rates of basins and sub-basins were calculated and it was verified that the existing open channels have a low slope with the presence of permanent water and generate stagnation of water favored by the presence of trash. It is proposed for the output of storm drains, the use of an existing channel to evacuate the flow. The solution proposed in this work is complemented by the placement of three pumping stations: one on a channel to drain rain water which will allow the drain of the excess water from the lower area where is located the Ingeniero White city and the two others that will drain the excess liquid from the port area.